Fetal Growth Restriction: Mechanisms, Epidemiology, and Management - Hester D. Kamphof; Selina Posthuma; Sanne J. Gordijn; Wessel Ganzevoort; Dandan Shi; Yiyuan Jiang (Wolters Kluwer Health, 2022)
Abstract. Fetal growth restriction (FGR) is the condition in which a fetus does not reach its intrinsic growth potential and in which the short-term and long-term risks of severe complications are increased. FGR is a frequent complication of pregnancy with a complex etiology and limited management options, other than timely delivery. The most common pathophysiological mechanism is placental insufficiency, due to many underlying causes such as maternal vascular malperfusion, fetal vascular malperfusion and villitis. Identifying truly growth restricted fetuses remains challenging. To date, FGR is often defined by a cut-off of the estimated fetal weight below a certain percentile on a population-based standard. However, small fetal size as a single marker does not discriminate adequately between fetuses or newborns that are constitutionally small but healthy and fetuses or newborns that are growth restricted and thus at risk for adverse outcomes. In 2016, the consensus definition of FGR was internationally accepted to better pinpoint the FGR population. In this review we will discuss the contemporary diagnosis and management issues. Different diagnostic markers are considered, like Doppler measurements, estimated fetal growth, interval growth, fetal movements, biomarkers, and placental markers.